2015
DOI: 10.1002/jcb.24995
|View full text |Cite
|
Sign up to set email alerts
|

Early Gene Expression in Salivary Gland After Isoproterenol Treatment

Abstract: Isoproterenol, a β-adrenergic agonist, has been shown to induce salivary gland hyperplasia. However, the mechanism involved in this pharmacological phenomenon is not well understood. To gain a better understanding of the underlying changes, including genes, networks and pathways altered by isoproterenol, microarray-based gene expression analysis was conducted on rat parotid glands at 10, 30, and 60 minutes after isoproterenol injection. After isoproterenol treatment, the number of differentially expressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A possible explanation for premature differentiation is that some of these signaling pathways are affected ( Román-Trufero et al, 2009 ). Indeed, we found that multiple early immediate genes, associated with cell growth/proliferation and cell death/survival functions, were downregulated in PIC cultured organoids suggesting an affected mechanotransduction ( Zhou et al, 2015 ). Upon stimulation of the signaling pathway involved in the expression of IEGs with isoproterenol ( Bahrami and Drabløs, 2016 ), the observed increase in organoid forming efficiency of PIC-cultured organoids point towards the potential to adapt the culture medium specifically for PIC gels to optimize stem cell self-renewal.…”
Section: Discussionmentioning
confidence: 96%
“…A possible explanation for premature differentiation is that some of these signaling pathways are affected ( Román-Trufero et al, 2009 ). Indeed, we found that multiple early immediate genes, associated with cell growth/proliferation and cell death/survival functions, were downregulated in PIC cultured organoids suggesting an affected mechanotransduction ( Zhou et al, 2015 ). Upon stimulation of the signaling pathway involved in the expression of IEGs with isoproterenol ( Bahrami and Drabløs, 2016 ), the observed increase in organoid forming efficiency of PIC-cultured organoids point towards the potential to adapt the culture medium specifically for PIC gels to optimize stem cell self-renewal.…”
Section: Discussionmentioning
confidence: 96%
“…Isoproterenol administration, interestingly, also induced ductal cell proliferation in rat SGs ( Hand and Ho, 1985 ). Expression of diverse cell growth, proliferation, and survival genes in rat SG has also been reported post isoproterenol treatment ( Yeh et al., 2012 ; Zhou et al., 2015 ), although whether these pertain to the acinar or ductal cell compartment is unclear. Chronic loss of sympathetic autonomic innervation leads to significant atrophy of parotid glands ( Proctor et al., 1988 ), but the effect of chronic application and withdrawal of β-blockade on function of the SG is not substantiated.…”
Section: Introductionmentioning
confidence: 99%